Detective effort: what contributes to arrests during retrospective criminal investigations? - Fallik, Seth W. (Policing and society, 2018)
Clearance rates among retrospective criminal investigations have been a cause for concern in the last 20 years. Unfortunately, little is known about how detectives contribute to case outcomes. To explore this topic, 184 detectives during a 60 day period completed time-task logs that were paired with incident report data. Through a unique temporal sampling procedure, 564 index offenses were disaggregated into subsamples based on the case’s suspect status at the time the case was assigned. The curvilinearity of these estimates was tested and recalculated into binary terms when quadratic relationships were observed. Continuous and re-estimated quadratic variables were then evaluated for multivariate suitability and regressed to predict a cases likelihood of arrest. The results of these analyses found that (a) detectives continue to exercise great investigative discretion once cases are assigned; (b) suspect status influences arrests; (c) detective time spent interviewing the suspect was the most consistent predictor of arrests; (d) the influence of individual investigative activities on arrests tended to vary by the suspect status; (e) detective effort matters most among cases without a known suspect; and (f) more time performing investigative activities is not always positively associated with arrests. These findings are discussed as they relate to organisation issues, such as supervision, case management, and resource allocation within the context of criminal investigations. In doing so, this quantification of detective effort contributes to policy and practice debates on detective caseloads and seeks to improve the efficacy of criminal investigations.